18F-DOPA PET/CT Physiological Distribution and Pitfalls: Experience in 215 Patients. (October 2016) - Calabria, Ferdinando F.; Chiaravalloti, Agostino; Jaffrain-Rea, Marielise L.; Zinzi, Maddalena; Sannino, Pasqualina; Minniti, Giuseppe; Rubello, Domenico; Schillaci, Orazio
Abstract : Purpose: 18 F-DOPA PET/CT is potentially helpful in the management of patients with low-grade brain tumors, movement disorders, and somatic neuroendocrine tumors. We describe the whole-body physiological distribution of 18 F-DOPA uptake. Patients and Methods: We examined 215 patients with 18 F-DOPA PET/CT. Among these, 161 had brain scans and 54 had whole-body scans. Results: Physiological distribution was negligible in the brain, with the exception of basal ganglia, whereas greatest activity was noted in the liver, pancreas, other exocrine glands, and the urinary system. Incidental tracer uptake sites were identified in 5.5% of patients. Some of these findings were due to inflammation, whereas in most cases, uptake was seen in benign tumors of the brain or in the endocrine or exocrine glands. Conclusions: 18 F-DOPA uptake may be seen in inflammatory tissue or benign tumors. Correlations with history, physical examination, laboratory examination, CT, MRI, and histology are necessary for optimal diagnosis.